Dismantling of the DIORIT research reactor - Conditioning of activated graphite. (January 2019) - Sierra Perler, Isabel Cecilia; Beer, Hans-Frieder; Müth, Joachim; Kramer, Andreas
Abstract: The research reactor DIORIT at the Paul Scherrer Institute was a natural uranium reactor moderated by D2 O. It was put in operation in 1960 and finally shut down in August 1977. The dismantling project started in 1982 and could be successfully finished on September 11th, 2012. About 40 tons of activated reactor graphite had to be conditioned during the dismantling of this research reactor. The problem of conditioning of activated reactor graphite had not been solved so far worldwide. Therefore a conditioning method considering radiation protection and economic aspects had to be developed. As a result, the graphite was crushed to a particle size smaller than 5 mm and added as sand substitute to a specially developed grout. The produced graphite concrete was used as a matrix for embedding dismantling waste in containers. By conditioning the graphite conventionally, about 58.5 m 3 (13 containers) of waste volume would have been generated. The new PSI invention resulted in no additional waste caused by graphite. Consequently, the resulting waste volume, as well as the costs, were substantially reduced. Highlights: About 45 tons of activated reactor graphite had to be conditioned during the dismantling of the research reactor DIORIT. A new conditioning method considering radiation protection and economic aspects had to be developed. The graphite concrete was used as a matrix for embedding dismantling waste in containers. The resulting waste volume, as well as the costs, were substantially reduced. The developed method was accepted by the Swiss Federal Nuclear Safety Inspectorate (ENSI) and the final disposer in Switzerland NAGRA (National Cooperative for the Disposal of Radioactive Waste). By applying the new method, the resulting waste volumes, as well as the costs, were reduced substantially.